Pengaruh Produksi Jerami Padi dan Jumlah Kepemilikan Sapi Potong terhadap Pemanfaatan Jerami Padi sebagai Pakan Sapi Potong - Amas, Akmal Fikri; Wijaya, Andis; Rahmadani, A.; Maharani, Nur Fadilah; Akbar, Andi Muh; Syamsu, Jasmal Ahmari (Jurnal Peternakan Lokal, 2025)
This study aims to analyze the effect of rice straw production and beef cattle population on the level of rice straw utilization as feed in Cenrana District, Bone Regency. The research was conducted through a survey method involving 40 farmer-respondents and employed a quantitative approach using multiple linear regression analysis. The findings indicate that farmers are generally of productive age and possess substantial experience in both farming and livestock, although the majority have a low level of formal education. Rice straw production reached 83,646.20 tons of dry matter with a carrying capacity of 36.68 AU (Animal Units), yet its utilization as feed remains suboptimal due to limited processing facilities and technology. The regression analysis revealed that rice straw production (X?) had a significantly positive effect on utilization (?? = 0.049; p < 0.001), while cattle population (X?) showed a negative and statistically insignificant effect (?? = -0.012; p = 0.576). This indicates that the availability of straw affects the utilization of rice straw as feed. However, the number of cattle owned does not affect the increase in the processing capacity and utilization of rice straw as feed for beef cattle.